THE CVD VARIABLES METHOD FOR TAILORING HFCVD CARBON NANOTUBE MORPHOLOGY - Hussain, Ashfaq (European Scientific Journal, ESJ, 2014)
In research on carbon nanotube growth by hot filament chemical vapor deposition (HFCVD), variations of HFCVD have yielded promising results. However, these systems have used plasma enhancement to tailor nanotube morphology. The use of plasma enhancement has made these HFCVD systems expensive to operate and difficult to scale up. This report presents research results to show that it is possible to use the inherent capabilities of variation in CVD parameters like pressure, temperature, and gas composition to tailor nanotube growth in the HFCVD system without resorting to additional cumbersome techniques, thus retaining the value of HFCVD as a low cost and scalable method.